Antimicrobial peptides: mechanism of action, activity and clinical potential - Zhang, Qi-Yu; Yan, Zhi-Bin; Meng, Yue-Ming; Hong, Xiang-Yu; Shao, Gang; Ma, Jun-Jie; Cheng, Xu-Rui; Liu, Jun; Kang, Jian; Fu, Cai-Yun (Military medical research, 2021)
The management of bacterial infections is becoming a major clinical challenge due to the rapid evolution of antibiotic resistant bacteria. As an excellent candidate to overcome antibiotic resistance, antimicrobial peptides (AMPs) that are produced from the synthetic and natural sources demonstrate a broad-spectrum antimicrobial activity with the high specificity and low toxicity. These peptides possess distinctive structures and functions by employing sophisticated mechanisms of action. This comprehensive review provides a broad overview of AMPs from the origin, structural characteristics, mechanisms of action, biological activities to clinical applications. We finally discuss the strategies to optimize and develop AMP-based treatment as the potential antimicrobial and anticancer therapeutics.